Study of Authority from a Civil Law Perspective - Ayu Vijaya Laksmi, Dyah (International Journal of Social Science, Education, Communication and Economics, 2025)
The concept of authority plays a pivotal role in the context of civil law, particularly in delineating the powers and responsibilities vested in legal subjects through statutory provisions. This research explores the nuanced distinctions between "authority" and "competence," asserting that authority in civil law is a formal power granted by legislation, whereas competence refers to the scope and nature of the duties assigned. The study adopts a qualitative approach, utilizing descriptive analysis to investigate the legal foundations and implications of authority, particularly its attribution, delegation, and mandate in the legal system. The findings emphasize the complex interplay between state sovereignty and civil law, illustrating how authority functions within legal relationships and its relevance in ensuring accountability. This paper further examines how civil law governs the delegation of authority, its implications for legal subjects, and the underlying principles that guide such delegation. Ultimately, this research contributes to the broader discourse on authority in civil law, highlighting the essential role of legal frameworks in governing power delegation while maintaining legal order and justice.